The Legality of Land Transactions with Certificates Encumbered by Mortgage Rights - Dwiputranto, Aditya; Tjempaka (Jurnal Cakrawala Hukum, 2024)
The sale and purchase of land in Indonesia, particularly when a mortgage right encumbers the land certificate, often gives rise to legal complications. This study examines the legal validity of land sale transactions in which the mortgage has not been officially discharged (Roya). By analyzing court rulings and statutory regulations, the study aims to provide insights into the implications of such transactions, especially concerning the protection of creditor rights and legal certainty for buyers. This research employs a normative legal research method, focusing on applicable legal norms and their implementation in practice. The results show that while the sale of land encumbered by a mortgage may be considered legally valid if the parties involved have fulfilled the basic requirements of agreement, capacity, a specific object, and lawful cause as stipulated in Article 1320 of the Civil Code, the transaction remains legally risky if the mortgage is not officially discharged. This study contributes to the discussion of agrarian law in Indonesia by offering a deeper understanding of the legal nuances of land transactions burdened by a mortgage. It provides recommendations for legal practitioners, academics, and other relevant parties.